Multidimensional analysis of conventional and electronic cigarette consumption among students - Țîru, Carmen Maria; Coman, Claudiu; Dalban, Costel Marian; Bătrânu-Pințea, Vlad; Anton, Mihail; Gherheș, Vasile; Obadă, Daniel-Rareș; Otovescu, Adrian (Frontiers in Psychology, 2026)
IntroductionCigarette consumption among university students remains a complex public health issue, encompassing both conventional and electronic products. This study investigates the multidimensional aspects of cigarette use among young adults, with a particular focus on psychosocial, perceptual, and behavioral determinants influencing nicotine consumption.MethodsA quantitative, cross-sectional design was employed. Data were collected through a standardized online questionnaire administered to 267 students enrolled in higher education institutions in Brașov, Romania. Descriptive statistics, correlation analyses, and ANOVA were used to identify consumption patterns, differentiate user types (current smokers, former smokers, and non-smokers), and examine emotional and motivational factors associated with tobacco and e-cigarette use.ResultsFindings indicate that traditional cigarette smoking is most frequently initiated under social influence, whereas electronic cigarette use is primarily associated with aesthetic appeal and flavor variety. Psychological motivations, particularly stress relief and social comfort, show significant correlations with continued nicotine use, especially among current smokers. Analysis informed by the Theory of Planned Behavior and Social Cognitive Theory highlights the role of behavioral intention and self-efficacy in sustaining smoking behaviors.DiscussionThe results underscore the multifaceted nature of smoking behavior among youth populations, revealing a dynamic interplay between cognitive, emotional, and environmental variables. These findings provide empirical support for the development of targeted intervention strategies and emphasize the need for integrated public health policies that address both product regulation and psychosocial education.